'Twisting the lion's tail': Manipulationist tests of causation for psychological mechanisms in the occurrence of delusions and hallucinations. (March 2019) - Brown, P.; Waite, F.; Freeman, D.
Abstract: Over the past 20 years the importance of psychological processes in psychosis has gained increasing attention. However, it is key to determine the causal status of these processes in order to inform understanding and identify treatment targets. Studies that directly manipulate a psychological mechanism provide the most robust causal evidence. This review evaluates for the first time the extent of manipulationist causal evidence for the role of specific psychological mechanisms in delusions and hallucinations. A systematic search identified controlled experiments or targeted interventions that both manipulated a specific psychological mechanism and measured the effect on individual psychotic experiences. Forty-three manipulationist studies were found of which 40 measured paranoia, 11 measured hallucinations, and two measured grandiosity. Twenty-eight studies were experiments and 15 were targeted intervention trials. Only 18 used clinical samples. Manipulation of the specified psychological mechanism was demonstrated in 35 cases. Of these, 28 found a subsequent change in a psychotic experience. Negative affect and related psychological processing in relation to paranoia have been most tested. There is a small body of direct causal evidence for the role of psychological mechanisms in psychotic experiences – that highlight important novel treatment directions – but the manipulationist approach has been used too infrequently. Highlights: Manipulationist-causal studies testing delusions and hallucinations are gathered. Forty-three studies manipulated psychological processes for psychotic experiences. Successful manipulation of a mechanism typically led to change in psychotic experiences. The studies potentially provide important treatment techniques. Causal tests are far too few, despite the potential for understanding and treatment.